Understanding the Health Impact of Packed Food Sauces Using Artificial Intelligence Driven Nutritional Score Generation - Kusuma, Talluri (Digital Repository of Theses, 2024)
The health effects of pre-packaged sauces on our meals may be substantial. A number of health issues, including diabetes, obesity, hypertension, and heart disease, are exacerbated by the abundance of sugar, salt, and bad fats in many of these sauces. A nutritional score for pre-packaged sauces may be generated using artificial intelligence (AI). A score indicating the product's total nutritional value may be generated by the AI system after it analyses the sauce's nutritional composition, including its constituents. Our machine learning system will take into account the sauce's calorie count, sugar content, salt content, and harmful fat content, among other things, to arrive with a nutritious score. Nutrients that are useful, like water, minerals, etc., may also be considered by the algorithm. The nutritional score may then be used to assist customers in making educated food selections. Soy sauces, for instance, may have their nutritional scores shown on the packaging so that buyers can quickly and easily compare them. Healthy food product development is another area that might benefit from the nutritional score. Food producers may find ways to make sauces healthier by comparing their nutritional composition. This helps them to create sauces with less sugar, salt, and bad fats